Human Atrial Fibrillation Is Not Associated With Remodeling of Ryanodine Receptor Clusters - Munro, Michelle L.; van Hout, Isabelle; Aitken-Buck, Hamish M.; Sugunesegran, Ramanen; Bhagwat, Krishna; Davis, Philip J.; Lamberts, Regis R.; Coffey, Sean; Soeller, Christian; Jones, Peter P. (Frontiers in Cell and Developmental Biology, 2021)
The release of Ca2+ by ryanodine receptor (RyR2) channels is critical for cardiac function. However, abnormal RyR2 activity has been linked to the development of arrhythmias, including increased spontaneous Ca2+ release in human atrial fibrillation (AF). Clustering properties of RyR2 have been suggested to alter the activity of the channel, with remodeling of RyR2 clusters identified in pre-clinical models of AF and heart failure. Whether such remodeling occurs in human cardiac disease remains unclear. This study aimed to investigate the nanoscale organization of RyR2 clusters in AF patients – the first known study to examine this potential remodeling in diseased human cardiomyocytes. Right atrial appendage from cardiac surgery patients with paroxysmal or persistent AF, or without AF (non-AF) were examined using super-resolution (dSTORM) imaging. Significant atrial dilation and cardiomyocyte hypertrophy was observed in persistent AF patients compared to non-AF, with these two parameters significantly correlated. Interestingly, the clustering properties of RyR2 were remarkably unaltered in the AF patients. No significant differences were identified in cluster size (mean ~18 RyR2 channels), density or channel packing within clusters between patient groups. The spatial organization of clusters throughout the cardiomyocyte was also unchanged across the groups. RyR2 clustering properties did not significantly correlate with patient characteristics. In this first study to examine nanoscale RyR2 organization in human cardiac disease, these findings indicate that RyR2 cluster remodeling is not an underlying mechanism contributing to altered channel function and subsequent arrhythmogenesis in human AF.